Biology Of Corcyra Cephalonica Stainton (Lepidoptera: Pyralidae) On Several Types Of Feed Media - Yulio Runtu; Jackson F. Watung; Robert W. Tairas (Jurnal Agroekoteknologi Terapan, 2023)
Corcyra cephalonica is one of the insect pests that attack food commodities in storage houses. The use of different feed media will affect the biology of C. cephalonica. This study aims to determine the biological differences of C. cephalonica by using several types of feed media. This study used a completely randomized design (CRD) method with 3 treatments and repeated 4 times consisting of A = 500 grams of rice bran feed media, B = 500 grams of corn bran media, and C = 500 grams of mixed bran feed media. The results showed that the number of eggs produced in rice bran was 388.25 grains, corn bran 346.00 grains, and mixed bran 344.50 grains. The egg stage in each treatment feed medium occurred for 3-4 days. The larval stage of rice bran occurred for 31.00 days, corn bran for 25.00 days and mixed bran 28.00 days. Pupa stage in rice bran occurred for 9.50 days, corn bran 7.50 days and mixed bran 8.50 days. The female stage of rice bran occurred for 6.25 days, maize bran 9.50 days and mixed bran 8.25 days. Meanwhile, the male stage of rice bran took 6.00 days, maize bran 8.75 days and mixed bran 7.25 days. The length of eggs produced by C. cephalonica on rice bran feed media ranged from 0.26-0.35 mm, corn bran ranged from 0.29-0.38 mm and mixed bran ranged from 0.28-0.37 mm. The sex ratio produced on rice bran feed media was 1:0.79, corn bran 1:1.12 and mixed bran 1:0.76. The developmental life span of C. cephalonica in rice bran was 44.50 days, maize bran 36.75 days and mixed bran 40.50 days. Keywords: Biology, Corcyra cephalonica, feed media Abstrak Corcyra cephalonica merupakan salah satu serangga hama yang menyerang komoditas pangan di gudang penyimpanan. Penggunaan media pakan berbeda akan mempengaruhi biologi C. cephalonica. Penelitian ini bertujuan untuk mengetahui perbedaan biologi C. cephalonica dengan menggunakan beberapa jenis media pakan. Penelitian ini menggunakan metode Rancangan Acak Lengkap (RAL) dengan 3 perlakuan dan di ulang sebanyak 4 kali yang terdiri dari A = media pakan dedak padi 500 gram, B = media dedak jagung 500 gram dan C = media pakan dedak campuran 500 gram. Hasil penelitian menunjukkan untuk jumlah telur yang dihasilkan pada dedak padi sebanyak 388,25 butir, dedak jagung 346,00 butir dan dedak campuran 344,50 butir. Stadium telur di setiap media pakan perlakuan terjadi selama 3-4 hari. Stadium larva pada dedak padi terjadi selama 31,00 hari, dedak jagung selama 25,00 hari dan dedak campuran 28,00 hari. Stadium pupa pada dedak padi terjadi selama  9,50 hari, dedak jagung 7,50 hari dan dedam campuran 8,50 hari. Stadium imago betina pada dedak padi terjadi selama 6,25 hari, dedak jagung 9,50 hari dan dedak campuran 8,25 hari. Sedangkan untuk stadium imago jantan pada dedak padi terjadi selama 6,00 hari, dedak jagung 8,75 hari dan dedak campuran 7,25 hari. Panjang telur yang dihasilkan oleh C. cephalonica pada media pakan dedak padi berkisar 0,26-0,35 mm, dedak jagung berkisar 0,29-0,38 mm dan dedak campuran berkisar 0,28-0,37 mm. Nisbah kelamin yang dihasilkan pada media pakan dedak padi yakni 1:0,79, dedak jagung 1:1,12 dan dedak campuran 1:0,76. Lama perkembangan hidup C. cephalonica pada dedak padi terjadi selama 44,50 hari, dedak jagung 36,75 hari dan dedak campuran 40,50 hari. Kata Kunci: Biologi, Corcyraa cephalonica, Media Pakan